High‐level soluble expression of Serratia marcescens H30 lipase in Escherichia coli. (17th July 2014) - Su, Erzheng; Xu, Jingjing; Wu, Xiangping
Abstract Serratia marcescens lipase (SmL) is an important biocatalyst used to enantioselectively hydrolyze (±)‐trans‐3‐(4‐methoxyphynyl) glycidic acid methyl ester. However, the economically justified level recombinant soluble expression of SmL in Escherichia coli has not been established. Thus, fusion genes of lipase from S. marcescens H30 with different fusion tags were constructed and expressed in E. coli. The effects of fusion tags were revealed. A significant increase in recombinant lipase solubility showed that E. coli BL21 (DE3)/pET32a‐SmL was a suitable choice for SmL production. To optimize the performance of recombinant SmL production, changes in culture medium compositions and induction conditions were systematically tested. Finally, the recombinant SmL activity and productivity reached approximately 23, 000 U/L and 1, 278 U/L/H in shake flasks, respectively. This value is the highest SmL activity attained by heterogeneous recombinant expression in E. coli. Lipase activity and productivity reached 19, 650 U/L and 1, 228 U/L/H, respectively, by scaling up SmL production in a 7.0 L fermenter. The existence of the Trx tag did not influence the chiral selectivity of recombinant SmL. These findings indicate a possibility for soluble and economical SmL expression in E. coli to meet industrial needs.